2022
DOI: 10.1029/2022gl099571
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Distributions of Auroral Kilometric Radiation in Earth's Northern and Southern Hemispheres Observed by the Arase Satellite

Abstract: Auroral kilometric radiation (AKR) is generated at high latitudes and can propagate down to low latitudes. Due to the lack of direct observations, the characteristics of AKR in the middle and low latitudes of two hemispheres have not been studied so far. Here, using observations of the Arase satellite from 23 March 2017 to 31 July 2019, we present the first statistical study of AKR distribution in the northern (Magnetic latitude Mlat = 0°–40°) and southern (Mlat = −40°–0°) hemispheres. Results (totally 30,353 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…1. From the figure, it can be seen that the asymmetric Laplace distribution is a skewed distribution with sharp peaks and thick tails, and the shape of the skewness is closely related to its quantile  [24][25][26]. In addition, the form of its distribution is quite different from the normal distribution, which shows that we also illustrate the difference between quantile regression and mean regression from the point of view of likelihood.…”
Section: Bayesian Hierarchical Quantile Regressionmentioning
confidence: 84%
“…1. From the figure, it can be seen that the asymmetric Laplace distribution is a skewed distribution with sharp peaks and thick tails, and the shape of the skewness is closely related to its quantile  [24][25][26]. In addition, the form of its distribution is quite different from the normal distribution, which shows that we also illustrate the difference between quantile regression and mean regression from the point of view of likelihood.…”
Section: Bayesian Hierarchical Quantile Regressionmentioning
confidence: 84%
“…Recently, Zhang et al (2021) have presented a concise model for the field-aligned distribution of R-X mode amplitude in the region of L = 3.0-6.2 and Magnetic Latitude (MLAT) = 0-± 40°. Based on observations from spacecrafts, some works have found the annual and seasonal periodic variations of R-X mode (Green et al, 2004;Kumamoto et al, 2003;Kumamoto & Oya, 1998;Mogilevsky et al, 2005;Xiao et al, 2022). Recently, Kumamoto et al (2018) have reported an AKR event with R-X and L-O modes simultaneously using the data from Arase satellite.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2021) have constructed a concise empirical formula for the field-aligned distribution of AKR based on Arase satellite and Van Allen Probes. Recently, statistical results have presented the asymmetric distributions of AKR based on observations of the Arase satellite (Xiao et al 2022). Previous numerous works have emphasized the importance of the interplanetary magnetic field (IMF) to the magnetosphere (Han et al 2017(Han et al , 2018Hu et al 2021).…”
Section: Introductionmentioning
confidence: 99%